Optimization of Hatching Rate in Zebrafish (Danio rerio) Through Aquatic Plant Substrate Combinations - Galih Faadihillah; Rangga Idris Affandi; Muhammad Junaidi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Fisheries are an important sector in providing animal protein sources and supporting national food security. The success of fish reproduction is a crucial factor that determines the continuity of production and the sustainability of cultivation businesses. Zebrafish (Danio rerio) is a freshwater fish that is often used in biomedical research and reproductive biology due to its fast reproductive cycle, embryo transparency, and ease of maintenance process. The study was conducted for 45 days at Andar Farm Lingsar. The method used was an experimental Completely Randomized Design (CRD) consisting of 6 treatments and 3 replications, resulting in 18 experimental units. The treatments tested were a combination of various types of aquatic plants. The parameters measured included fecundity growth, fertilization rate, hatching rate, and gonadosomatic index. Data analysis was performed using ANOVA. If there were significant differences, Duncan's further test was used to identify significantly different treatments. The results showed that in the fecundity parameter, the Water hyacinth + cabomba substrate type produced the highest fecundity (117.6 ± 13.0 grains). In terms of Fertilization Rate (FR) and Hatching Rate (HR), the water hyacinth substrate produced the highest FR (79.96%), and HR (62.47%). Meanwhile, the Gonadosomatic Index (GSI) parameter also produced the highest results in the combination of water hyacinth + cabomba (20.4%). Water quality obtained during the study was within the optimal range with a temperature of 25-26 oC, Ph 7, and 6 mg/L.